The Concept of The Islamic Education Curriculum According to Ibn Khaldun and Its Relevance to Islamic Education in The Modern Era - Muhammad Yusron Maulana El-Yunusi; Mardiyah Mardiyah (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2026)
This study aims to examine Ibn Khaldun’s views on the concept of an Islamic educational curriculum as a reference for contemporary education. This research uses a library research (literature review) approach. Primary data were obtained from Ibn Khaldun’s main work, Al-Muqaddimah, while secondary sources were collected from relevant journals and books discussing his educational thought. Data were collected through documentation techniques focusing on comprehensive and modern educational perspectives. The data were analyzed using content analysis to systematically identify key ideas, which were then synthesized to strengthen the study's theoretical framework. The findings show that Ibn Khaldun’s curriculum emphasizes balance between religious (sharīʿah) sciences and rational or philosophical sciences. This balance does not imply equal portions but highlights the importance of integrating various fields of knowledge so that students develop a holistic understanding. Ibn Khaldun also stressed that knowledge should not be dichotomized, as all sciences contribute to human intellectual and moral development. Furthermore, Ibn Khaldun’s concept of curriculum remains relevant to modern Islamic education. His ideas align with the goals of national education, particularly the view that education focuses on developing the whole person. Humans are seen as integrated beings consisting of intellectual, spiritual, and social dimensions that must be developed harmoniously through education.